Correlation and prediction of arterial partial pressure of carbon dioxide from venous umbilical blood gases - Thatrimontrichai, Anucha; Charernjiratragul, Kan; Janjindamai, Waricha; Dissaneevate, Supaporn; Maneenil, Gunlawadee; Phatigomet, Manapat; Anantasit, Nattachai (The Turkish Journal of Pediatrics, 2022)
Background. Arterial partial pressure of carbon dioxide (pCO 2 ) samples are lower in children and higher in fetuses when compared with venous samples. The correlation and prediction of pCO 2 from umbilical venous (UVBG) to umbilical arterial blood gas (UABG) dyad in neonates are identified. Methods. A prospective study was performed from July 2018 to December 2019. Two dependent tests and a multivariate regression model were used to analyze the comparison and correlation tests. Results. A total of 116 paired UABG and UVBG samples were obtained. The medians (interquartile ranges, IQR) were as follows: gestational age of 34 (29-37) weeks, birth weight of 2122 (1146-2839) g, and postnatal age of 2.3 (1.4-10.8) h. The median (IQR) pCO 2(UABG) and pCO 2(UVBG) measurements were 40.2 (33.5-45.8) and 40.4 (34.7-46.8) mmHg, respectively (rho = 0.75, p < 0.001). The median of the differences (IQR) in pCO 2(UABG) and pCO 2(UVBG) was -0.9 (-4.7 to 2.3) mmHg, (p = 0.06). The equation to predict pCO 2(UABG) was 0.9 × pCO 2(UVBG) + 4, as derived from simple linear regression. The best model for predicting pCO 2(UABG) was 0.9 x pCO 2(UVBG) - 0.7 × venous base excess + 0.6 × 5-min Apgar score + 6.1 × meconium aspiration syndrome - 7.7 × patent ductus arteriosus - 6.5 (adjusted r < sup > 2 < /sup > = 0.74). Conclusions. pCO 2(UVBG) correlates with and can predict pCO 2(UABG) . Therefore, pCO 2(UVBG) can be applied to pCO 2(UABG) in neonates for whom UAC insertion is unsuccessful or to avoid an arterial puncture.